Socjologia języka — szkic modelu teoretycznego subdyscypliny socjologii kultury - Ziółkowski, Marek (Wydział Prawa i Administracji UAM, 1975)
In the paper the general outline of the theoretical model of the sociology of language is presented. Language is a very important social factor that must be taken into account in every sociological analysis of the social structure on the macro-level as well as of social action of the individual in face-to-face interaction. Purely linguistic analysis, being very subtle and precise, is nevertheless insufficient from this point of view. Since the times of de Saussure linguistics concentrated on so called langue (language), a set of rules conceived of as social norm that is never actually fulfilled. But for sociologist much more interesting is the very act of speaking (parole), occurring in a given social context, and all the social regularities that control the linguistic behaviour and can explain in every case, its particular features. In the first part of the paper the notion of speech community is introduced and the lingustic repertoire is defined, as well as linguisitic varieties and their dimensions of diversity (geographical, social and temporal). So called standard language ist examined. This analysis points out the heterogenity and diversity of linguistic patterns Within the society, and tries to indicate the social factors accounting for this phenomenon. The language of a given individual (idiolect) is described as the result of the influences of different social groups. The notion of sociolinguistic competence is introduced. The popular beliefs and attitudes to linguistic behaviour are presented as a domain of so-called folk-linguistics. In the second part the model of a speech act and all its elements (from R. Jakobson) is developed. The notion of speech variant is proposed, conceived of as the patterning of speech evoked by specific sociolinguistic situation. Different types of speech variant are enumerated. Eventually the notions of linguistic variety and speech variants are related to the concepts of langue and parole.
The Sociology of Language — the Draft of Theoretic Model of the Subdiscipline of the Sociology of Culture
Keywords: IS